BUDAYA SEKOLAH, SERVANT LEADERSHIP DAN KEPUASAN KERJA TERHADAP KINERJA GURU SD SE-KECAMATAN SUNGAI MAS KABUPATEN ACEH BARAT - Adnan, Muhammad; Najmuddin, Najmuddin; Musrizal, Musrizal (IndOmera, 2024)
The research aims to conduct an empirical study analysis of school culture, Servant Leadership and job satisfaction on their influence on teacher performance. Survey research of 89 elementary school teachers in Sungai Mas District, West Aceh Regency. The research was carried out descriptively associative, with problem analysis using a statistical multiple regression analysis approach. Descriptive research results show: (1) teachers' perceptions of the condition of school culture that they feel and implement are good with an achievement level of 87.34%.  Also, the principal's Servant Leadership factor is generally good, and the teacher's job satisfaction achievement level is 86.49%. (2) school culture, Servant Leadership and job satisfaction provide a positive influence in improving teacher performance, with their respective influence values ​​through the regression model: Y = 29.291 + 0.466 X1 + 0.274 X2 + 0.379 X3.  (3) it is proven that school culture factors, the principal's servant leadership and job satisfaction together make a significant contribution to teacher performance, with an amount of 74.2%.